2022
DOI: 10.1186/s12883-022-02751-w
|View full text |Cite
|
Sign up to set email alerts
|

Influences of different referral modes on clinical outcomes after endovascular therapy for acute ischemic stroke

Abstract: Background and purpose As endovascular thrombectomy (EVT) is time-dependent, it is crucial to refer patients promptly. Current referral modes include Mothership (MS), Drip and Ship (DS) and Drive the Doctor (DD). The purpose of this study was to investigate the influences of different referral modes on the clinical outcomes of patients with acute ischemic stroke after EVT.  Methods A total of 349 patients from 15 hospitals between April 2017 and Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
7
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 47 publications
1
7
2
Order By: Relevance
“…In some of these observational studies, the secondary transfer model showed a lower percentage of patients receiving IVT [14], while others observed higher rates of IVT in this model [16]. In our cohort, we did not find significant differences in this regard.…”
Section: Discussioncontrasting
confidence: 57%
See 2 more Smart Citations
“…In some of these observational studies, the secondary transfer model showed a lower percentage of patients receiving IVT [14], while others observed higher rates of IVT in this model [16]. In our cohort, we did not find significant differences in this regard.…”
Section: Discussioncontrasting
confidence: 57%
“…However, the relative benefit from the MT did not differ significantly in the two groups [13]. Other real-life studies with a design similar to ours have not reported significant differences in the functional outcome, substantial recanalization, or symptomatic hemorrhagic transformation between the two transfer models, although the process times were longer in the secondary transfer groups in most cases [14][15][16][17][18][19][20][21].…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…The data of our study was collected from Beijing Chaoyang hospital of Capital Medical University and medical consortium. The statistical results showed that the OGT of our study was longer than other studies [ [9] , [10] , [11] , [12] ]. Our center has established an integrated health care system with PSC, and medical conditions in capital of China is developed relatively.…”
Section: Discussioncontrasting
confidence: 48%
“…[36][37][38] Time is brain; we should spare no effort to help reduce procedural times and LKNPT through workflow optimization with multidisciplinary collaboration, reduce infarct volume and early prediction to improve endovascular time metrics and patient outcomes. [39][40][41][42][43] DRT and PRT can be further shortened through the standardization of acute stroke workflows to improve patient outcomes. 40 The main limitations of this study include its retrospective study design and small sample size.…”
mentioning
confidence: 99%